2012
DOI: 10.1371/journal.ppat.1002803
|View full text |Cite
|
Sign up to set email alerts
|

A Cytotoxic Type III Secretion Effector of Vibrio parahaemolyticus Targets Vacuolar H+-ATPase Subunit c and Ruptures Host Cell Lysosomes

Abstract: Vibrio parahaemolyticus is one of the human pathogenic vibrios. During the infection of mammalian cells, this pathogen exhibits cytotoxicity that is dependent on its type III secretion system (T3SS1). VepA, an effector protein secreted via the T3SS1, plays a major role in the T3SS1-dependent cytotoxicity of V. parahaemolyticus . However, the mechanism by which VepA is involved in T3SS1-dependent cytotoxicity is unknown. Here, we found that protein transfection of VepA into HeL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 54 publications
0
44
1
Order By: Relevance
“…It is made up of two heterologous subunits: The cytoplasmic V 1 domain hydrolyzes ATP, which energizes the translocation of protons through the membrane-bound V o proton channel, and into the lumen of the acidic organelle. A recent study indicated that the Vibrio effector VopQ (vp1680, VepA) interacts with Vma3p (subunit c) of the highly conserved V-ATPase V o proton translocation domain (6). Our analyses revealed that HisVopQ interacts with Vma6 (subunit d) of the V o domain when incubated with highly enriched preparations of yeast vacuoles (Fig.…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…It is made up of two heterologous subunits: The cytoplasmic V 1 domain hydrolyzes ATP, which energizes the translocation of protons through the membrane-bound V o proton channel, and into the lumen of the acidic organelle. A recent study indicated that the Vibrio effector VopQ (vp1680, VepA) interacts with Vma3p (subunit c) of the highly conserved V-ATPase V o proton translocation domain (6). Our analyses revealed that HisVopQ interacts with Vma6 (subunit d) of the V o domain when incubated with highly enriched preparations of yeast vacuoles (Fig.…”
Section: Resultsmentioning
confidence: 50%
“…A previous report suggested that VopQ causes rupture of lysosomes in vivo and in vitro, resulting in the release of luminal enzymes (6). Because our findings are in direct contrast to this previously published work, we revisited these studies.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Similarly, the cytotoxicity of enniatin mycotoxins (Ivanova et al, 2012), and venom toxins from cobra (Feofanov et al, 2005) and South American rattlesnake (Hayashi et al, 2008), have been connected with LMP. Additionally, Vibrio parahaemolyticus VepA was recently identified as a new type of LMP-inducing protein (Matsuda et al, 2012). After inoculation, VepA binds to the cytoplasmic tail of the channel-forming subunit c of vacuolar H + -ATPase and triggers leakage of lysosomal hydrolases into the cytosol in a manner that depends on the subunit c. It will be of great interest to investigate whether VepA causes the widening of the ATPase channel and whether other LMP-inducing stimuli utilize a similar mechanism.…”
Section: Bacterial Fungal and Snake Toxinsmentioning
confidence: 99%
“…These findings unveil a novel activity of bacterial cholesterol-dependent cytolysins that may interfere with important host cellular pathways linked to lysosomal functions. So far, only few pathogenic bacteria were reported to target lysosomes by mechanisms differing from the one observed with L. monocytogenes [91][92][93][94][95].…”
Section: Interaction With Lysosomesmentioning
confidence: 98%